An investigation of parenting in relation to motor and language development in young children - Roberts, Christina Lee (Curtin University, 2013)
Although previous studies have consistently documented that parent-child interaction plays a significant role in a child’s motor and language development, limited research has been undertaken to examine the possible causal relationships of these linkages by using different parenting measures. This study identified relationships between parenting, motor and language development using both a mother-report assessment and a naturalistic observational approach with mothers and their children age 4 to 6 years old.